A NEW TYPE OF SYNTHETIC XENOMINERAL INCLUSIONS IN DIAMOND - Silaev V.I.; Rakin V.I.; Filippov V.N.; Chaikovskiǐ I.I. (My University, 2004)
As result of the studies on the diamond crystal from eluvial-deluvial-proluvial Middle Urals placer deposit, revealed is new previously unknown class of syngenetic inclusions represented by Ti-Fe-Si-Zr-Al-oxide solid solutions. Analytical electron microscopy investigation of the inclusions morphology and composition suggests that the studied phases should be assigned to especial - juvenile - paragenesis class of syngenetic inclusions.